Burkholderia cepacia Complex Lumbar Spondylodiscitis: A Rare Nosocomial Infection - Rachel Subramanian; Lynn Fitzgibbons (Case Reports in Infectious Diseases)
Pyogenic spondylodiscitis is rarely caused by Burkholderia cepacia complex. B. cepacia is widespread in the environment and recognized as an opportunistic pathogen for patients with cystic fibrosis and immune disorders. A female in her mid-30s with underlying hyperthyroidism, but otherwise immunocompetent, was admitted to the hospital with persistent lower back pain after elective bariatric surgery in Mexico. Lumbar MRI showed L2/L3 osteomyelitis and discitis. Culture of disk aspiration grew Burkholderia cepacia complex sensitive to cefepime, ceftazidime, ciprofloxacin, gentamicin, imipenem, levofloxacin, and trimethoprim-sulfamethoxazole. The infection failed to respond to cefepime; however, she was successfully treated with levofloxacin monotherapy.